Effect of disease‐modifying anti‐rheumatic drugs on therapeutic outcomes among women with endometriosis1. Issue 2 (18th January 2018) - Kotlyar, Alexander; Shue, Shirley; Liu, Xiaobo; Falcone, Tommaso
Abstract: Objective: To determine whether disease‐modifying anti‐rheumatic drugs (DMARDs) affect the use of hormonal treatments, subsequent ablative surgery, and need for pain management, including opioids, non‐steroidal anti‐inflammatory drugs and anti‐depressants, among women with endometriosis. Methods: In a retrospective study, data were reviewed from women with surgically confirmed endometriosis who were not treated (n=234) or treated with DMARDs for 6 weeks or more (n=25) before surgical diagnosis at a single healthcare system in the USA between 2003 and 2013. The postoperative use of hormonal treatments, proportion of women undergoing subsequent ablative surgery, and use of adjunct therapies such as antidepressants, steroids, and opioids after surgery were compared between the two groups. Results: The two groups showed differences in age ( P =0.007) and follow‐up time ( P <0.001). Univariate analysis showed more frequent use of hormonal treatments ( P =0.045) and antidepressants ( P =0.006) among women treated with DMARDs. The frequency of post‐diagnostic use of opioids was lower among treated women ( P =0.001); this association remained significant in multivariate analysis controlling for potential confounders ( P =0.003). Conclusion: The findings suggest that administration of DMARDs for at least 6 weeks is associated with decreased opioid usage among women with endometriosis. Abstract : Among women with endometriosis, treatment with disease‐modifying anti‐rheumatic drugs for at least 6 weeks was associated with a lower frequency of opioid usage.